Engineering education through social innovation: the contribution of professional societies - Gorham, Douglas; Nwulu, Nnamdi (Lecture notes in networks and systems, 2020)
This book explores the nexus between professional technical societies and engineering education by examining several societies' efforts to promote and support engineering and engineering education in the areas of pre-university education, university education and informal education through programs and activities designed to leverage social innovation. Professional societies are in a unique position to support and contribute to engineering education, and have dedicated substantial resources to social responsibility programs and activities that promote engineers and engineering. The book is chiefly intended for engineers, engineering educators, staff members of professional technical societies, and for the broad range of scholars whose work involves technology education and education policy.
Keywords: Réservé UdeM